Micro-independent record labels in the UK: discourse, DIY cultural production and the music industry - Strachan, Robert (European Journal of Cultural Studies, 2012)
"This article examines the relationship between the practices of do-it-yourself (DIY) micro-independent record labels in the UK and wider mediated discourses surrounding the music industry. It is suggested that a heightened version of the art versus commerce dichotomy central to rock ideology provides the basis for a number of legitimizing theories through which the aesthetic and industrial conventions of these practitioners are justified and given importance. First, the article suggests that these legitimizing theories serve to narrow the scope of, and draw distinct boundaries around, small-scale cultural production. Second, through a self-conscious critique of globalized corporate media they serve as an engagement with the politics of cultural production and, ultimately, media power. Finally, using two prominent case studies relating to new technology (Arctic Monkeys and Clap Your Hands Say Yeah) the article examines the ways in which discourses relating to DIY cultural production impact upon mainstream music industry practice and discourse." [author's abstract]